Peran Empirisme dalam Transformasi Epistemologis Ilmu Humaniora Modern - Syifaudin Syifaudin (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study aims to analyze the role of empiricism in shaping the modernity of the humanities, particularly in terms of epistemological foundations, methodological practices, and the orientation of research objects. The study is based on the assumption that modern humanities are not entirely detached from scientific traditions, but rather developed through the adaptation of empirical principles within humanistic inquiry. This research employs a qualitative approach using a literature review and historical-conceptual analysis of major empiricist thinkers, such as John Locke, David Hume, and Auguste Comte, as well as relevant works in the philosophy of science and the history of the humanities. The findings indicate that empiricism significantly contributed to shifting the sources of valid knowledge in the humanities from traditional authority and metaphysical speculation toward empirical evidence and primary data. Furthermore, empiricism played an important role in the development of more systematic research methodologies, including source criticism in historiography, structured textual analysis in literary studies, and field-based observation in linguistics. The study also reveals that empiricism encouraged a redefinition of the objects of humanities research, directing scholarly attention toward concrete human experience and socio-historical realities. This study concludes that the modernity of the humanities did not emerge from a rejection of empiricism, but from a creative adaptation of empirical principles integrated with interpretative approaches. The contribution of this research lies in repositioning empiricism as a relevant epistemological foundation for the development of modern humanities.